AB0746 Apremilast, an Oral Phosphodiesterase 4 Inhibitor, and the Impact of Baseline Weight and BMI on ACR20 and HAQ-DI Response: Pooled Results from 3 Phase 3, Randomized, Controlled Trials. (10th June 2014) - Schett, G.; Mease, P.; Gladman, D.; Kavanaugh, A.; Adebajo, A.; Gomez-Reino, J.; Wollenhaupt, J.; Cutolo, M.; Lespessailles, E.; Hu, C.; Stevens, R.; Edwards, C.; et al.
Abstract : Background: Apremilast (APR), an oral phosphodiesterase 4 inhibitor, works intracellularly to regulate inflammatory mediators. PALACE 1, 2, and 3 compared the efficacy and safety of APR with placebo (PBO) in patients with active psoriatic arthritis (PsA) despite prior disease-modifying antirheumatic drugs and/or biologics. Objectives: Assess the impact of baseline weight and body mass index (BMI) on clinical response to APR over 24 weeks in a pooled analysis. Methods: Patients were randomized 1:1:1 to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline DMARD use (yes/no). Patients with <20% reduction from baseline in swollen or tender joint counts at Week 16 were required to be re-randomized to APR20 or APR30 if initially randomized to PBO, or continued on their initial APR dose. At Week 24, all remaining PBO patients were re-randomized to APR20 or APR30. Results: 1493 patients were randomized, received ≥1 dose of study medication (PBO: n=496; APR20: n=500; APR30: n=497), and were comparable across treatment groups for demographics, disease characteristics, and prior/concurrent therapy. At baseline, mean (SD) weight was 85.7 (20.6) kg and mean (SD) BMI was 29.9 (6.5) kg/m 2 . APR administration resulted in statistically significant and clinically meaningful improvement in ACR20 response (primary endpoint) in all 3 PALACE trials. APR30 was associated with significant improvements in Health Assessment Questionnaire-Disability Index (HAQ-DI) vs PBO at Week 16 (key secondary endpoint) across all 3 trials. At Week 16, similar ACR20 response rates and improvements in HAQ-DI were observed across all weight and BMI ranges (Table). A favorable treatment effect for both APR treatment groups vs PBO was observed, irrespective of baseline body weight or BMI. Overall, the treatment effect was dose-dependent, with greater effects generally observed in APR30 over APR20 patients. These treatment effects were generally maintained at Week 24. Conclusions: APR demonstrated a favorable treatment effect in patients with active PsA. Comparable improvements in the signs and symptoms of PsA and physical function were observed across a broad range of baseline weight and BMI values. Results suggest no dose adjustment is required to account for baseline body weight or BMI. Disclosure of Interest: G. Schett Grant/research support: Abbott, Celgene Corporation, Roche, P. Mease Grant/research support: Celgene Corporation, Novartis, and Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB, D. Gladman Grant/research support: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, A. Kavanaugh Consultant for: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, A. Adebajo: None declared, J. Gomez-Reino Grant/research support: Bristol-Myers Squibb, Roche, Schering-Plough, and Wyeth; and has received research grants from Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, and UCB SA, J. Wollenhaupt Grant/research support: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB, M. Cutolo Grant/research support: Actelion, Bristol-Myers Squibb, and, E. Lespessailles Grant/research support: Amgen, Eli Lilly, Novartis, and Servier, C. Hu Employee of: Celgene Corporation, R. Stevens Employee of: Celgene Corporation, C. Edwards Grant/research support: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, C. Birbara Grant/research support: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and DOI: 10.1136/annrheumdis-2014-eular.1773